2D thin sheets composed of Co5.47N–MgO embedded in carbon as a durable catalyst for the reduction of aromatic nitro compounds. (19th February 2021) - Jin, Chengxu; Gu, Ying; Li, Zhihui; Wang, Siyu; Wang, Nan; Jiao, Yanqing; Buhe, Bateer; Tian, Chungui
Abstract : 2D nanosheet composed of Co5.47 N–MgO embedded in carbon has been synthesized through the molten salt-assisted synthesis route, which can serve as a highly efficient and durable catalyst for the reduction of more than ten kinds of nitro-compounds. Abstract : Convenient high-yield synthesis of metal nitride-based materials with good stability is pursued constantly. Especially considering the advantages of 2D materials, the combination of cobalt nitride with 2D nanosheets is hoped to promote its catalytic ability, but the synthesis remains a challenge. Herein, we showed the feasible synthesis of 2D thin sheets composed of Co5.47 N–MgO embedded in carbon (2D Co5.47 N–MgO@C sheets) in high yield, which is based on a grinding treatment of Co salt and 2-methylimidazole (2-MIM) in MgCl2 /NaCl/KCl salts followed by two-step calcination. During the first nitridation step, 2-MIM, which had already been coordinated with Co and Mg, can convert into an amorphous carbon layer with the embedded Co species, along with the formation of MgO. During the next step, Co5.47 N can be generated in tight connection with the amorphous carbon layer and MgO. The molten salt medium can induce the orientated growth of the material and prevent it from agglomeration, even in the case of a high Co concentration, thus realizing the high-yield synthesis and dispersion of the 2D sheets. Remarkably, the present synthetic strategy exhibits high conversion (almost 100%) of the added Co source into cobalt nitride. The reduction of an aromatic nitro compound (4-nitrophenol, 4-NP) into an amine compound (4-aminophenol, 4-AP) was used to evaluate the catalytic performance. 4-NP was effectively converted. The alkalinity of MgO is favourable for the deprotonation of 4-NP, which enhances the activity. Notably, there was no obvious change in performance after recycled use up to 10 times owing to the protection of carbon. Furthermore, tests confirmed that the 2D Co5.47 N–MgO@C sheets exhibit excellent catalytic performance for the reduction of a series of nitro compounds. The present method provides a promising route for the convenient synthesis of 2D nanosheet-based catalysts.